2013
DOI: 10.1016/j.bjane.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Routine Testing in Low-risk Patients Undergoing Minor and Medium Surgical Procedures

Abstract: We found that preoperative additional tests are excessively ordered, even for young patients with low surgical risk, with little or no interference in perioperative management. Laboratory tests, besides generating high and unnecessary costs, are not good standardized screening instruments for diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Furthermore, positive findings do not necessarily produce a change in anesthetic practice. 32 Frequently, preoperative routine blood tests appear to be justified by legal, rather than medical, reasons. 33 Typically, undirected laboratory screening does not reveal unknown pathologies, even in patients with prevalent bleeding disorders, such as von Willebrand disease.…”
mentioning
confidence: 99%
“…Furthermore, positive findings do not necessarily produce a change in anesthetic practice. 32 Frequently, preoperative routine blood tests appear to be justified by legal, rather than medical, reasons. 33 Typically, undirected laboratory screening does not reveal unknown pathologies, even in patients with prevalent bleeding disorders, such as von Willebrand disease.…”
mentioning
confidence: 99%
“…The high rate of abnormal electrocardiographic findings is not unique to this retrospective review; several other studies have found similar rates of abnormality [24−28]. In a prospective study evaluating the outcome of preoperative evaluations for ASA 1 patients undergoing elective noncardiac surgery, de Sousa Soares et al [24] found that 62% of patients underwent ECG preoperatively; 6.86% of tests were abnormal, and only 0.51% led to a change in patient management. Both studies provide evidence that the clinical usefulness of routine ECG in low-risk patients is negligible because the difference in cardiovascular death in patients with and without electrocardiographic abnormalities is very low [27].…”
Section: Electrocardiographymentioning
confidence: 60%
“…In fact, our next step will involve the introduction of a clinical decision supporting rule (CDSR) through electronical request when ordering POTs in order to report and/or cancel tests when previous pathological results within 6 months are expected or known. Our study nowadays stands as one of the studies with more patients included as far as we know ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%